2017
DOI: 10.1038/ja.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

Fradiamine A, a new siderophore from the deep-sea actinomycete Streptomyces fradiae MM456M-mF7

Abstract: New bioactive substances were identified from several marine actinomycetes strains by LC-HRESI-MS based non-targeted metabolomics. A new siderophore and its derivative, named fradiamines A and B, were isolated from the extract of the deep-sea actinomycetes Streptomyces fradiae MM456M-mF7 by Diaion CHP-20P, Sephadex LH-20 column chromatography and HPLC. Fradiamine A was a new compound, but fradiamine B was previously patented as a sweetness enhancer. Their structures were determined by NMR and LC-HRESI-MS/MS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Fradiamine A (2) and B are natural siderophores produced by the deep-sea Streptomyces fradiae MM456M and have shown moderate antibiotic activity against Clostridium difficile [45]. Other examples of siderophores isolated from marine environment are the catechol-type siderophore, streptobactin (5) and benarthin (6), isolated from Streptomyces sp.…”
Section: Streptomyces: a Natural Source Of Siderophores Among Bacteriamentioning
confidence: 99%
“…Fradiamine A (2) and B are natural siderophores produced by the deep-sea Streptomyces fradiae MM456M and have shown moderate antibiotic activity against Clostridium difficile [45]. Other examples of siderophores isolated from marine environment are the catechol-type siderophore, streptobactin (5) and benarthin (6), isolated from Streptomyces sp.…”
Section: Streptomyces: a Natural Source Of Siderophores Among Bacteriamentioning
confidence: 99%
“…A new siderophore and its derivative, designated as fradiamines A (24) and B (25), were recently found to be produced by Streptomyces fradiae MM456M-mF7, isolated from the deep-sea sediment sample collected at a depth of 806 m in the Sagami Bay, Japan. Fradiamines A and B displayed moderate antibacterial activity against Clostridium difficile BAA-1382 with IC 50 values of 32 and 8 μ g·ml −1 , respectively [82].…”
Section: Novel Antibacterial and Anticancer Compounds From Culturmentioning
confidence: 99%
“…It has, however, been found that a number of earlier reported NPs attributed to sponges are in fact biosynthesized by their endosymbionts [162], many of which are Actinomycetes. Through the utilization of metabolomics along with other omics tools, marine Actinomycetes have been explored and profiled [163][164][165][166][167] while many new potential drugs [112,113,117,160,162,[168][169][170][171][172][173][174] and agrochemicals [175] have been recently described. For the purpose of this literature appraisal, three research papers were selected and analyzed to assess the application of metabolomics to current drug discovery programs, with a particular focus on novel antibiotics isolated from marine Streptomyces.…”
Section: Marine Bacteriamentioning
confidence: 99%